Biosynthesis of Conjugated Linoleic Acid (CLA): A Review - Khanal, R.C.; Dhiman, T.R. (Pakistan Journal of Nutrition, 2004)
Conjugated linoleic acid is a mixture of positional and geometric isomers of linoleic acid with two conjugated unsaturated double bonds at various carbon positions in the fatty acid chain. An increasing interest on CLA is attributed to its potential health benefits such as anticarcinogenic, antiatherogenic, antidiabetic and antiadipogenic effects. More than a dozen isomers of CLA are present in ruminant fat. Of the two isomers known for their physiological importance, c-9, t-11 is the most prevalent one comprising 80 to 90% of total CLA in food products from ruminants, whereas t-10, c-12 is present in small amounts at 3-5% of total CLA. Sequences in the biohydrogenation of dietary unsaturated fatty acids leading to the biosynthesis of CLA in the rumen from linoleic acid and in the mammary gland from t-11 C18:1 by delta-9 desaturase have been reviewed. Understanding the mechanisms involved in the biosynthesis of CLA will allow us to design feeding strategies for enhancing the concentration and output of CLA in milk and meat so we can derive the potential health benefits associate with it.